The effect of coconut water on alleviating menstrual pain (dysmenorrhea) in teenage women - Luky Febriani; Elly Wahyuni; Afrina Mizawati (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: World Health Organization (WHO) in 2018 stated that the number of dysmenorrhea in the world is very large, on average more than 50% of women in each country experience dysmenorrhea. In the United States, it is estimated that almost 90% of women experience dysmenorrhea and 10-15% of them experience dysmenorrhea severe, which causes them to be unable to carry out any activities. Purpose: To find out